PENGARUH MODEL PEMBELAJARAN TERHADAP HASIL BELAJAR MATA KULIAH PENGEMBANGAN MEDIA DAN SUMBER BELAJAR - Muhammad Isnaini; Nadiroh Nadiroh; Moch. Sukardjo (Chemistry Education Department of Education and Teaching Faculty, 2020)
This study aimed to determine the differences in learning outcomes of media development courses and learning material between groups of students who are taught using guided inquiry learning models compared to groups of students who are taught using discovery learning models. Research approaches conducted by researchers using quantitative descriptive methods. The object of research conducted on students in the media development and learning material subject in the one of Study Program at UIN Raden Fatah Palembang. Analysis of the data and formulas used to test hypotheses using t-test which first performed an analysis of the normality of the data, a homogeneity. Based on the measurement results of the Islamic Education student learning outcomes, the researcher can conclude that the discovery learning and guided inquiry learning model influences of learning outcomes. The data analysis and formula used were normality test, homogeneity test and then hypothesis testing. Based on the results of the measurement of learning outcomes, the researcher can conclude that there are differences in learning outcomes using the discovery learning model and the inquiry learning model in the course of media development and learning resources. This is shown from the calculation results, namely the significance value which is below 0.05, which is equal to 0.000. It is hoped that other researchers can develop other studies that focus on other thinking skills such as critical thinking.